Biodegradasi Bioplastik Berbasis Pati Menggunakan Isolat Fungi Indigenous Asal Tempat Pembuangan Akhir Gunung Tugel, Kabupaten Banyumas - Jimmy Al Fa'is; Ratna Stia Dewi; Ajeng Arum Sari (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
The use of plastic in Indonesia, especially as packaging, is very popular among the public, because it is practical and has many uses. Plastic consumption in 2020 even reached 67.8 million tons per day. Therefore, one way to overcome this problem is to use and produce biodegradable plastics or bioplastics. Biodegradation of bioplastics can be done with fungi. The potential place to find bioplastic degrading fungi is the Gunung Tugel Ex-Final Disposal Site (TPA). Considering the fact that bioplastiks have a fairly good level of degradation, in this study a starch-based biodegradation test will be carried out using isolats of indigenous fungi originating from Ex-TPA Gunung Tugel using the method of calculating the weight loss of bioplastics (weight loss). This study aims to obtain starch-based bioplastic degrading fungi isolats from Ex-TPA Gunung Tugel, Banyumas Regency and determine the highest biodegradability ability of starch-based bioplastics by fungal isolats from Ex-TPA Gunung Tugel, Banyumas Regency. The results showed that isolats of indigenous fungi that had the potential to degrade starch-based bioplastics from Ex-TPA Gunung Tugel, Banyumas Regency were obtained from the genus Aspergillus (GT2 isolate) and Penicillium (GT1, GT3, GT4, GT5, and GT6) isolate. The highest biodegradability of starch-based bioplastics was found by fungi from the genus Aspergillus, namely isolate GT2 with a weight loss of 21.84%. The biodegradation occurs due to the activity of endoamylase, exoamylase, and glucanase enzymes produced by fungi. The observation of the texture of the bioplastic resulted in a significant change in color, namely from the white bioplastic sheet to brownish. These observations also showed the attachment of fungal mycelium on the surface of the bioplastik accompanied by a hollow and uneven surface of the bioplastikc. Keywords : Biodegradation, Starch-based bioplastik, Indigenous Fungi, TPA.